Implementation, Challenges, and Cost Model for Calculating Investment Solutions of Business Process Intelligence - Sundjaja, Arta M. (PROCEEDING IC-ITECHS 2014, 2014)
The increasing implementation of BPM and BI in the enterprise,make top managementrequires measurement the performance of business process. The problems that perceived by them ishow to integrating data which from different systemsand process it into an information that can support the decision-making to improve the performance of business processes. The writer tries to explain some of the implementation of BPI on companies in Germany and Australia, challenges that perceived by managementin design, developmentand implementation of BPI in the company and then how to calculate dan analyze invesmen tof BPI solutions.